1985
DOI: 10.1111/j.1600-0528.1985.tb01687.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological indicators of fluoride exposure and utilization: an epidemiological study

Abstract: Individual samples of urine, fingernails, head-hair, saliva, plaque and enamel were collected from three groups of Hungarian children, aged 14 years, who were exposed to contrasting water fluoride levels (less than or equal to 0.11 ppm; 0.5-1.1 ppm; 1.6-3.1 ppm). The mean fluoride concentration of the samples increased consistently and significantly, but mostly non-proportionately, with increasing water fluoride level. With the exception of plaque, the materials examined are considered suitable indicators of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 10 publications
(3 reference statements)
0
38
1
6
Order By: Relevance
“…Dental fluorosis had been reported historically in three locations in Hungary associated with high-fluoride waters, the water sources in these areas have since been altered and the disease is no longer prevalent (Toth, 2000). In a study of 3 groups of Hungarian children aged 14 exposed to contrasting fluoride concentrations in drinking water, Schamschula et al (1985) demonstrated a link between high fluoride contents and community fluorosis index values but the index values were too low (< 0.6) to constitute a public health problem.…”
Section: Fluorosis Prevalencementioning
confidence: 99%
“…Dental fluorosis had been reported historically in three locations in Hungary associated with high-fluoride waters, the water sources in these areas have since been altered and the disease is no longer prevalent (Toth, 2000). In a study of 3 groups of Hungarian children aged 14 exposed to contrasting fluoride concentrations in drinking water, Schamschula et al (1985) demonstrated a link between high fluoride contents and community fluorosis index values but the index values were too low (< 0.6) to constitute a public health problem.…”
Section: Fluorosis Prevalencementioning
confidence: 99%
“…19 Para el ceo-d los estratos socioeconómicos con mayor proporción de caries dental fueron el bajo (1 y 2) con 32,2% y el medio (3 y 4) con 26,1%, lo que coincide con lo observado por schamschula y colaboradores quienes manifestaron que el desarrollo económico y la condición socioeconómica son factores fuertemente relacionados con la etiología de la caries dental puesto que los niños de estrato socioeconómico alto tienen mayor posibilidad de realizar su higiene bucal con pasta de dientes con flúor y de forma frecuente. 20 Con respecto al cepillado, los hallazgos de este estudio coinciden con lo reportado por un estudio en Taiwán que encontró una fuerte asociación entre la frecuencia del cepillado de los dientes y la prevalencia de caries dental; así mismo observaron que los niños que no se cepillaban los dientes antes de ir a la cama presentaban más lesiones de caries dental. 7 En cuanto a los valores del índice de placa, hubo una mediana correlación con el índice ceo-d, lo que se explica porque la placa bacteriana es una causa necesaria, más no suficiente para el desarrollo de caries dental y es más importante su composición que su cantidad.…”
unclassified
“…An additional daily intake of 3.0 mg fluoride over 30 days resulted immediately in a 90% increase of the basal urinary fluoride excretion and three months later in an increase of the fluoride content of fingernails (Whitford et al, 1999b). Subjects living in areas with high fluoride content in water (1.6-3.1 mg/L) had 1.8 and 2.9 times higher fluoride contents in fingernails than subjects from areas with intermediate (0.5-1.1 mg/L) and low (<0.11 mg/L) fluoride content in the water, respectively (Schamschula et al, 1985).…”
Section: Biomarkers For Fluoride Exposure and Statusmentioning
confidence: 95%
“…The fluoride content in enamel is indicative of the amount taken up during tooth formation, whereas the surface layers of enamel of erupted teeth is affected by the fluoride concentrations in the mouth. The fluoride content in enamel biopsies from 137 children aged 14 years at 0.44-0.48 μm and 2.4-2.6 μm depth was proportional to the fluoride content of the drinking water (0.09 versus 1.9 mg/L: 1549 and 641 versus 3790 and 2110 mg/kg, respectively) (Schamschula et al, 1985). Dentine, which like bone slowly increases in fluoride content throughout life and, unlike bone, does not undergo resorption, is probably the most suitable indicator of chronic fluoride intake.…”
Section: Biomarkers For Fluoride Exposure and Statusmentioning
confidence: 98%
See 1 more Smart Citation